Rapid and Sensitive Detection of Vibrio vulnificus Using CRISPR/Cas12a Combined With a Recombinase-Aided Amplification Assay - Xiao, Xingxing; Lin, Ziqin; Huang, Xianhui; Lu, Jinfang; Zhou, Yan; Zheng, Laibao; Lou, Yongliang (Frontiers in Microbiology, 2021)
Vibrio vulnificus is an important zoonotic and aquatic pathogen and can cause vibriosis in humans and aquatic animals (especially farmed fish and shrimp species). Rapid and sensitive detection methods for V. vulnificus are still required to diagnose human vibriosis early and reduce aquaculture losses. Herein, we developed a rapid and sensitive diagnostic method comprising a recombinase-aided amplification (RAA) assay and the CRISPR/Cas12a system (named RAA-CRISPR/Cas12a) to detect V. vulnificus. The RAA-CRISPR/Cas12a method allows rapid and sensitive detection of V. vulnificus in 40 min without a sophisticated instrument, and the limit of detection is two copies of V. vulnificus genomic DNA per reaction. Meanwhile, the method shows satisfactory specificity towards non-target bacteria and high accuracy in the spiked blood, stool, and shrimp samples. Therefore, our proposed rapid and sensitive V. vulnificus detection method, RAA-CRISPR/Cas12a, has great potential for early diagnosis of human vibriosis and on-site V. vulnificus detection in aquaculture and food safety control.